Fish oil as effective supplement preventing inflammatory and histopathological alterations in adjuvant-induced arthritis in rats (Research, Society and Development, 2021)
In this study was investigated the effect of treatment with a fish oil preparation (FOP) on inflammatory and histopathological parameters in a rat model of adjuvant-induced arthritis (AIA). Paw edema, the severity of secondary lesions, the number of synovial leukocytes, and serum nitric oxide and cytokines concentrations were evaluated. Histological changes in cartilage and bone of the femorotibial articulation in the paws were analyzed by hematoxylin/eosin and sirius red-hematoxylin staining. Oral treatment with the FOP (75, 150, and 300 mg/kg) that was initiated on the day of arthritis induction (day zero) and maintained for 21 days inhibited inflammatory signals and prevented morphological changes in cartilage and bone of the femorotibial articulation of the paws. These effects could be at least partially attributable to inhibitory and modulatory actions of the FOP on the production and release of nitric oxide and cytokines that participate in the pathophysiology of AIA.